Bilateral saccular inguinal hernias in an elderly woman presenting with advanced ovarian cancer. (27th January 2014) - Burke, Thomas Patrick; Waters, Peadar; Khan, Waqar; Barry, Kevin
Abstract : We present a case of an elderly woman presenting with bilateral groin hernias, one reducible and the other irreducible. CT of the abdomen and pelvis demonstrated an irreducible left inguinal hernia containing an incarcerated loop of transverse colon together with saccular metastatic tumour spread. Disseminated omental disease and ascitic fluid were noted throughout the peritoneal cavity secondary to ovarian carcinoma. As a consequence of extensive malignant disease and advanced age, the patient was treated conservatively and subsequently died a number of weeks later. To the best of our knowledge, this is only the second case of bilateral inguinal hernias presenting in a woman with a background of disseminated ovarian malignancy. This case highlights the importance of pre-reduction imaging in atypical complex cases.